2017
DOI: 10.4236/ns.2017.94010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Sago Palm (Metroxylonsagu Rottb.) Progenies with Natural Pollination by Using RAPD Markers

Abstract: Sago palm is flowering and fruiting just once in their life cycle. Sago palms that grow naturally and semi cultivated were generally occurred natural pollination to form fruits and seeds, if not cut down to take the starch contained in their trunk. Sago palm pollination may occur as self-pollinated and cross-pollinated. If cross-pollinated was occurred in the pollination process, it will be varied of their progenies. This study aims to reveal the genetic variation of sago palms progenies with naturally pollina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This opinion was consistent with Lengkong and Runtunuwu (2005) who reported that the genetic diversity among West African Tall coconut seedlings was quite high, the diversity was estimated due to seeds derived from open pollination so that individual coconut has a different genotype from one to another. In the related study, it was reported that the seedlings of sago palm derived from seeds were differentiated (Abbas et al 2017). This phenomenon shows that generally, sago palm in the natural condition was the result of cross-pollination.…”
Section: Genetic Characters Of Sago Seedlingsmentioning
confidence: 92%
“…This opinion was consistent with Lengkong and Runtunuwu (2005) who reported that the genetic diversity among West African Tall coconut seedlings was quite high, the diversity was estimated due to seeds derived from open pollination so that individual coconut has a different genotype from one to another. In the related study, it was reported that the seedlings of sago palm derived from seeds were differentiated (Abbas et al 2017). This phenomenon shows that generally, sago palm in the natural condition was the result of cross-pollination.…”
Section: Genetic Characters Of Sago Seedlingsmentioning
confidence: 92%
“…In recent years, the sago palm has been placed in the limelight of agricultural molecular research subsequent to the whole chloroplast genome sequencing, orgnanellar genome copy number investigation, genome survey, genome size estimation, population genetics, transcriptomics as well as proteomics (Wee & Roslan, 2012;Abbas et al, 2017;Lim et al, 2020a;Lim et al, 2020b;Nisar & Hussain, 2020;Lim et al, 2021). The origin of life is often associated with the central dogma of molecular biology and genes are deemed the building blocks of life.…”
Section: Data Descriptionmentioning
confidence: 99%
“…A single sago plant can yield approximately 200–250 kg of wet sago each year, which equates to 25 tons of dry starch per hectare. This starch contains 84.7 g of carbohydrates per 100 g [ 8 , 13 ]. Sago starch extraction employs various methods, ranging from traditional to semi-modern and modern techniques.…”
Section: Introductionmentioning
confidence: 99%